2018
DOI: 10.1152/physiolgenomics.00143.2017
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of human monogenic cardiomyopathy genes in experimental polygenic cardiac hypertrophy

Abstract: Hypertrophic cardiomyopathy thickens heart muscles, reducing functionality and increasing risk of cardiac disease and morbidity. Genetic factors are involved, but their contribution is poorly understood. We used the hypertrophic heart rat (HHR), a unique normotensive polygenic model of cardiac hypertrophy and heart failure, to investigate the role of genes associated with monogenic human cardiomyopathy. We selected 42 genes involved in monogenic human cardiomyopathies to study: 1) DNA variants, by sequencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Familial hypertrophic cardiomyopathy is most commonly linked with single-point sarcomeric mutations. In contrast, the rat model used in the present study is characterized by polygenic disruption causing cardiomyocyte early terminal differentiation and compensatory hypertrophy ( Porrello et al, 2009a ; Prestes et al, 2018 ). In addition, direct comparison of in vitro tissue efficiency and in vivo whole-heart efficiency requires careful consideration.…”
Section: Discussionmentioning
confidence: 96%
“…Familial hypertrophic cardiomyopathy is most commonly linked with single-point sarcomeric mutations. In contrast, the rat model used in the present study is characterized by polygenic disruption causing cardiomyocyte early terminal differentiation and compensatory hypertrophy ( Porrello et al, 2009a ; Prestes et al, 2018 ). In addition, direct comparison of in vitro tissue efficiency and in vivo whole-heart efficiency requires careful consideration.…”
Section: Discussionmentioning
confidence: 96%
“…conduction system diseases, atrial fibrillation, and ventricular tachycardia) are the main clinical signs that occur after the accumulation of misfolded TTR protein (52-54). Furthermore, transcriptomic interaction is observed between TTR and DSG2 to induce hypertrophic cardiomyopathy in animal models (55). In this context, methylation changes in DSC2 and DSG2 genes could reflect pathogenic processes in hATTR target organs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous microarray analysis on human serum revealed several circulating miRNAs, including miR-18a-5p, miR-30d-5p, miR-21-5p, miR-193-5p, miR-10b-5p, miR-15a-5p, miR-296-5p, and miR-29a-3p, were potential diagnostic biomarkers for diffuse myocardial fibrosis during HCM (13). Moreover, Prestes et al (14) reported a validated miRNA-mRNA network composed of two upregulated miRNAs, miR-34a-5p and miR-17-5p, and five targeted genes including Pkp2, Rbm20, Ryr2, Tpm1, and Vcl in hypertrophic heart rat. Yet so far, no systemic and detailed analysis of miRNA-mRNA regulatory network was conducted to improve the diagnostic method of HCM.…”
Section: Introductionmentioning
confidence: 96%